Party-Voter Linkage in Africa Ghana and Senegal in Comparative Perspective - Osei, Anja.; SpringerLink (Online service) (Wiesbaden : VS Verlag für Sozialwissenschaften, 2012)
Parties in Africa are often described as organisationally and programmatically weak. On the other hand, they mobilise substantial numbers of voters at election time. This contradiction provokes an interesting question: How do political parties in Africa relate to the society? How do they mobilise their voters and sympathisers, and which strategies do they employ? Anja Osei analyses how parties in Ghana and Senegal adapt to their local context by employing locally embedded strategies.
Conceptual Problems of Party Research in Africa -- Research Design and Methodology -- Background: Party Formation in Africa -- Democracy, the State and Political Parties in Africa Today -- Political Parties in Ghana -- Political Parties in Senegal -- Political Parties in Ghana and Senegal in a Comparative View -- Linkage Strategies in a Comparative View.
Keywords: Social sciences; Social Sciences; Comparative Politics; Political Science, general